Working and Living Conditions of Women Migrant Domestic Workers in Istanbul during the COVID-19 Pandemic - Hakan Bektaş; Berrin Oktay Yılmaz; Adviye Damla Ünlü Bektaş (Journal of Economy Culture and Society)
In the context of increasing international migration, the destructive force of the pandemic has been evident in the closure of borders and disruptions to travel plans, affecting millions of migrants worldwide. The economic and social consequences have deeply impacted vulnerable social groups such as women, migrants and precarious workers, further intensifying the ‘care crisis’. Women migrant domestic workers, constituting a significant proportion of international migrant workers, have found themselves particularly vulnerable while grappling with challenges such as health risks and economic and social impacts. In this context, this study explores the multifaceted impact of COVID-19 on the working and living conditions of women migrant domestic workers. The methodology employed a qualitative approach, with insights derived from in-depth interviews with 12 migrant domestic workers in Istanbul. The findings confirm precarious conditions and highlight deepening issues related to COVID-19. This reveals that their already precarious situation, characterized by low wages, job insecurity and inadequate access to protective equipment and health services, has been exacerbated by the pandemic. This article emphasizes the need to address the broader care crisis intensified by the pandemic.